A New Schiff Base Organically Modified Silica Aerogel-Like Material for Metal Ion Adsorption with Ni Selectivity - João P. Vareda; Paulo D. Matos; Artur J. M. Valente; Luisa Durães (Adsorption Science & Technology)
Nickel has several industrial uses and is a valuable metal, making its selective separation and recycling a priority goal. A novel adsorbent, a Schiff base organically modified silica (ORMOSIL) aerogel, was prepared, for selective nickel removal from wastewater with other metal ions, by including a salen ionophore in the silica-based network. The newly developed adsorbent takes advantage of the salen’s selectivity and of the high porosity of silica aerogels. The aerogel-like adsorbent was prepared via sol-gel chemistry, using a coprecursor approach and ambient pressure drying. The inclusion of the Schiff base in the silica network was accomplished by reacting an amine-containing silica precursor with an aldehyde and confirmed by nuclear magnetic resonance (NMR) analysis. The adsorbent shrunk only 10% after evaporative drying, which resulted in a highly porous material (85% porosity, 4 cm3 g−1 specific pore volume). The low surface area of 28 m2 g-1 was due to the predominantly macroporous structure of the material (mean pore diameter of 563 nm). Adsorption isotherms and kinetic curves with single and binary mixtures of cations at room temperature were used to assess the selectivity of the adsorbent. The adsorption follows a BET (Brunauer-Emmett-Teller) trend. Due to the proximity of the oxygen and nitrogen atoms in the salen and steric hindrance from their neighboring atoms, it is likely that only the smallest hydrated cations can act as a coordination center and interact with both donor atoms. Thus, nickel was fairly removed (50 mg g-1), while other cations barely interacted with the adsorbent (cadmium adsorption maximum of 5 mg g-1). The estimated selectivity coefficient for nickel ranges from 1.8, in relation to copper, to 9.4 relatively to cadmium, which can be relevant for the separation of nickel in several industrial contexts, for instance, from electroplating sludge.